Effectiveness of a self-rehabilitation program to improve upper-extremity function after stroke in developing countries: A randomized controlled trial - NIAMA NATTA, DIDIER; LEJEUNE, THIERRY; DETREMBLEUR, CHRISTINE; Yarou, Bérénice; SOGBOSSI, EMMANUEL; ALAGNIDE, Etienne; KPADONOU GODONOU, TOUSSAINT; Selves, Clara; STOQUART, GAETAN (My University, 2020)
Background: About two-thirds of stroke patients present long-term upper-limb impairment and limitations of activity, which constitutes a challenge in rehabilitation. This situation is particularly true in developing countries, where there is a need for inexpensive rehabilitation solutions. Objective: This study assessed the effectiveness of a self-rehabilitation program including uni- or bimanual functional exercises for improving upper-limb function after stroke with respect to the context in Benin, West Africa. Methods: In this single-blind randomized controlled trial, chronic stroke individuals (>6 months post- stroke) performed a supervised home-based self-rehabilitation program for 8 weeks (intervention group); the control group did not receive any treatment. Participants were assessed before treatment (T0), at the end of treatment (T1) and 8 weeks after the end of treatment (T2). The primary outcome was the manual ability of the upper limb, assessed with ABILHAND-Stroke Benin. Secondary outcomes were grip force, motor impairment (Fugl-Meyer Assessment – Upper Extremity), gross manual ability (Box and Block test, Wolf Motor Function test) and quality of life (WHOQOL-26). Results: We included 28 individuals in the intervention group and 31 in the control group. Adherence to the program was 83%. After 8 weeks of self-rehabilitation, individuals in the intervention group showed significantly improved manual ability and grip force as compared with the control group (P < 0.001), with effect size 0.75 and 0.24, respectively. In the intervention group, the difference in average scores was 10% between T0 and T1 and between T0 and T2. Subscores of physical and psychological quality of life were also significantly improved in the intervention group. The other variables remained unchanged. Conclusions: A self-rehabilitation program was effective in improving manual ability, grip force and quality of life in individuals with stroke in Benin. More studies are needed to confirm these results in different contexts.
Keywords: Stroke; Upper extremity; Self-management; Developing countries; International Classification of Functioning; Disability and Health; Quality of life